Pengaruh Inovasi Varian Rasa Terhadap Daya Tarik Dan Keunggulan Kompetitif UMKM Martabak Pecenongan 78 - Arafah, Luthfi; Setiadi, Galih; Putri, Sabrina Huswatun Hasanah Delia; Purwanti, Rica Dwi; Nur’ilah, Siti (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of flavor variant innovation on customer appeal and competitive advantage of the SME Martabak Pecenongan 78. In the increasingly competitive culinary industry, product innovation is a key strategy to attract consumer attention and create business differentiation. This research adopts a quantitative approach using a survey method through questionnaires distributed to customers who have tried more than one martabak flavor variant. The data were analyzed using multivariate linear regression and T-tests with the assistance of SPSS software. The results indicate that flavor variant innovation significantly influences both consumer appeal and competitive advantage, both partially and simultaneously. These findings highlight that diverse and innovative flavors can enhance consumer interest, satisfaction, and the SME’s strategic market position. Therefore, continuous development of flavor innovations is essential as a core strategy to maintain customer loyalty and achieve sustainable business competitiveness.